FIBROUS SILICA-HYDROXYAPATITE COMPOSITE BY ELECTROSPINNING - Garibay-Alvarado, Jesús Alberto; Espinosa-Cristóbal, León Francisco; Reyes-López, Simón Yobanny (International Journal of Research -GRANTHAALAYAH, 2017)
New nanocomposite membrane was fabricated by electrospinning. The nanocomposite combines a glass and hydroxyapatite (HA). This research proposed the incorporation of glass to counteract the brittleness of HA in a composite formed by coaxial fibers which will be used for bone replacement. Calcium phosphate ceramics are used widely for dental and orthopedic reasons, because they can join tightly through chemical bonds and promote bone regeneration. Precursors HA and SiO2 were synthetized through the sol-gel method and then incorporated into a polymeric PVP matrix; later they were processed by coaxial electrospinning to obtain fibers with an average diameter of 538 nm which were characterized with techniques such as Attenuated Total Reflectance-Fourier Transform Infrared Spectroscopy, Differential Thermal Analysis and Scanning Electron Microscopy. Chemical and physical characterization of the membranes evidenced fibers in a coaxial disposition with a glass core and hydroxyapatite cover. The micro-porous fibers have many potential uses in the repair and treatment of bone defects, drug delivery and tissue engineering. Through ATR-FTIR and SEM-EDX analysis the presence of characteristic chemical groups, the fiber composition and microstructure were determined.